Section 10.2. Homework #2 Masaya Sato7.
Let
z
be a ﬁxed element of the center of
R
. Prove that the map
m
→
zm
is an
R
-modulehomomorphism from
M
to itself. Show that for a commutative ring
R
the map from
R
toEnd
R
(
M
) given by
r
→
rI
is a ring homomorphism (where
I
is the identity endomorphism).
Proof.
We ﬁrst claim that
ϕ
:
M
→
M
deﬁned by
ϕ
(
m
) =
zm
, where
z
is some ﬁxed elementof the center
Z
(
R
) of
R
, is an
R
-module homomorphism. Then for all
m,n
∈
M
and all
r
∈
Rϕ
(
m
+
rn
) =
z
(
m
+
rn
) =
zm
+
z
(
rn
)=
zm
+ (
zr
)
n
=
zm
+ (
rz
)
m
=
zm
+
r
(
zm
)=
ϕ
(
m
) +
rϕ
(
m
)since
z
∈
Z
(
R
),
i.e.
z
commutes with every element in
R
under multiplication. So
ϕ
is an
R
-module homomorphism.Next suppose that
R
is a commutative ring and let Φ :
R
→
End
R
(
M
) be a map deﬁned byΦ(
r
) =
rI
,where
I
:
M
→
M
is the identity endomorphism. Then for all
r,s
∈
R
Φ(
r
+
s
) = (
r
+
s
)
I
=
rI
+
sI
= Φ(
r
) + Ψ(
s
)andΦ(
rs
) = (
rs
)
I
= (
sr
)
I
= (
rI
)(
sI
) = Ψ(
r
)Ψ(
s
)since
R
is commutative,
I
2
=
I
, and(
rI
)(
sI
)(
m
) = (
rI
)(
s
(
I
(
m
))) = (
rI
)(
I
(
sm
)) = (
rI
)(
sm
) = (
rsI
)(
m
)for every
m
∈
M
.
9.
Let
R
be a commutative ring. Prove that Hom
R
(
R,M
) and
M
are isomorphic as left
R
-modules. [Show that each element of Hom
R
(
R,M
) is determined by its value on the identityof
R
.
Proof.
Observe ﬁrst that Hom
R
(
R,M
) is an
R
-module, and deﬁne an
R
-module map Ψ :
→
Hom
R
(
R,M
)
→
M
byΨ(
f
) =
f
(1),where 1
∈
R
is the multiplicative identity. Also denote
o
∈
Hom
R
(
R,M
) is the zero function,
i.e.
o
(
r
) = 0 for all
r
∈
R
. If
f
∈
Hom
R
(
R,M
) is not the zero function, then Ψ(
f
) =
f
(1)
= 0since
f
(1) = 0 implies that
f
(
r
) =
f
(
r.
1) =
r.f
(1) = 0
∀
r
∈
R
.
Abstract Algebra
by Dummit and Foote 3